Making Los Angeles Home : The Integration of Mexican Immigrants in the United States - Alarcón, Rafael; Odgers, Olga; Escala-Rabadan, Luis, 1959- (Book collections on Project MUSE., 2016)
Making Los Angeles Home examines the different integration strategies implemented by Mexican immigrants in the Los Angeles region. Relying on statistical data and ethnographic information, the authors analyze four different dimensions of the immigrant integration process (economic, social, cultural, and political) and show that there is no single path for its achievement, but instead an array of strategies that yield different results. However, their analysis also shows that immigrants' successful integration essentially depends upon their legal status and long residence in the region. The book shows that, despite this finding, immigrants nevertheless decide to settle in Los Angeles, the place where they have made their homes.